An Efficient Synthesis of Novel Dihydrothiazol-2-yl-amides via Cyclisation of Propargylic Carbamothioyl-amides. (March 2014) - Saeedi, Mina; Goli, Fereshteh; Mahdavi, Mohammad; Sarihi, Pouria; Asadipour, Ali; Shafiee, Abbas; Foroumadi, Alireza
An efficient protocol is described for the versatile synthesis of novel dihydrothiazol-2-yl-amide derivatives via the regioselective 5-exo-dig heterocyclisation of N -propargyl carbamothioyl-amides in the presence of 1, 4-diazabicyclo[2.2.2]octane (DABCO) in refluxing ethanol. All products were obtained in good yields and short reaction time (10–30 min).